Electrodialysis - Yonar, Taner (IntechOpen, 2020)
The electrodialysis process, from energy to the environment, offers very important opportunities. Separation of ion content in water, recovery, electrolysis of water, and many other possibilities will be possible with electrodialysis. Electrodialysis is of great importance not only in the efficient use of resources in our world, but also in space studies. In this book on electrodialysis, in 7 chapters, the possibilities offered by the electrodialysis process are discussed in detail and presented to the service of the scientific community.